(untitled) (Global Journal of Science Frontier Research, 2014)
In the present work domino reaction of indole with homophthaladehyde (1) have been investigated for the first time. The reaction have been done in presence of glacial acetic acid as catalyst and solvent afford the novel un probable mixture of two isomers A and B of benzo[7]anulene (2) that couldn’t be divided accompany with the formation of the predictable tetraindole (3) in a yield of 46 to 38 % respectively. Terephthaladehyde (4) condensed with indoles in glacial acetic acid in a molar ratio (1:4) affording compounds 5 a,b in a high yield of 93 -95 % after a short time of stirring at room temperature. Compounds 5 a,b can act as nucleophile due to the unoccupied two positions of the four indole rings. Accordingly we now present for the first time a expedient method for the synthesis of the novel extensive ring systems 6 and (7 a-f ) via condensation reaction of compound 5 a with aryl or heteroaryl substituted aldehydes in a molar ratio (1:2).